2011
DOI: 10.1080/17461391.2010.506661
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity levels during Dutch primary and secondary school physical education

Abstract: Objective: Physical education (PE) has been attributed an important role in providing young people with physical activity. If sufficiently active, PE lessons could contribute to physical activity levels in youth. Therefore, the purpose of this study was to determine the overall intensity of Dutch primary and secondary school physical education (PE) lessons and the influence of various lesson characteristics on these intensity levels. Methods: Between September 2008 and June 2009 heart rates were measured using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 32 publications
4
32
0
Order By: Relevance
“…Fairclough and Stratton (2005b), in discussing their finding that boys displayed higher physical activity levels than girls in PE, acknowledged that lesson content might have had an effect on their results, with girls being exposed to content that did not lend itself to engagement in MVPA. Slingerland et al (2011), echoing earlier findings of Kulinna et al (2003) and Laurson et al (2008) among this age group, found that boys were more active than girls during team game activities, while girls were more active than boys during individual activities. The findings of Sarradel et al (2011), on the other hand, indicated that girls were more active than boys across both games and non-games content.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Fairclough and Stratton (2005b), in discussing their finding that boys displayed higher physical activity levels than girls in PE, acknowledged that lesson content might have had an effect on their results, with girls being exposed to content that did not lend itself to engagement in MVPA. Slingerland et al (2011), echoing earlier findings of Kulinna et al (2003) and Laurson et al (2008) among this age group, found that boys were more active than girls during team game activities, while girls were more active than boys during individual activities. The findings of Sarradel et al (2011), on the other hand, indicated that girls were more active than boys across both games and non-games content.…”
Section: Discussionsupporting
confidence: 73%
“…Heart rate monitoring facilitates an individual assessment of the physiological demand of an activity on the participant (Simons-Morton, 1988) and is therefore widely used to measure students' activity during PE (e.g Fairclough & Stratton, 2005a, 2005bJago et al, 2009;Kulinna, Martin, Lai, Kliber & Reed, 2003;Racette et al, 2015;Sarradel et al, 2011;Slingerland et al, 2011). However, interpreting the results of the heart rate studies is problematic as many different interpretations of the heart rate threshold for MVPA have been used (Epstein at al., 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that less than half of the time of the PE lessons is of moderate-to-vigorous intensity in both primary and secondary school. 34 Next, during PE lessons or during recess, attention should also go to the children who are not already active. Girls are currently a bit neglected in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…The Actiheart device objectively and validly measures physical activity levels [12] and has been proven to be a feasible instrument in researching children and adolescents [13][14][15][16][17]. The Actiheart device was attached to participants' chest using two ECG electrodes ( Figure 1).…”
Section: Participantmentioning
confidence: 99%